First record of the mealybug, Rastrococcus tropicasiaticus Williams (Hemiptera: Pseudococcidae) in Indonesia - Zarkani, Agustin; Sunardi, Tri; Nadrawati,; Djamilah,; Ercan, Cansu; Kaydan, Mehmet Bora (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
Rastrococcus is a spectacular genus with no close relatives of the family Pseudococcidae that have unique truncate-conical cerarian setae. The survey studies were conducted through random observation on some woody plants in Bengkulu province, southern Sumatra island from 2019 to 2020. The study recorded a presence of Rastrococcus tropicasiaticus Williams (Hemiptera: Pseudococcidae) in Indonesia for the first time. It was found on Azadirachta excelsa (Meliaceae), Cerbera manghas (Apocynaceae), Dimocarpus longan (Sapindaceae), Ficus sp. (Moraceae), and Tectona grandis (Lamiaceae). The highest mealybug incidence was found on A. excelsa and C. manghas with 80% and 30% of attacks, respectively.